Innovative Therapy for Alzheimer’s Disease-With Focus on Biodelivery of NGF - Mitra, Sumonto; Behbahani, Homira; Eriksdotter, Maria (Frontiers in Neuroscience, 2019)
Alzheimer's disease (AD) is a devastating neurological condition associated with abnormal protein modification, inflammation and memory impairment. Aggregated amyloid beta (Aβ) and phosphorylated tau proteins are medical diagnostic features but detected only after the disease has progressed to advanced stages. The loss of memory in AD has been associated with central cholinergic dysfunction in the basal forebrain, where the cholinergic circuitry projects to the cerebral cortex and hippocampus. Current medications target acetylcholine metabolism to stabilize memory decline. Various reports link AD progression with declining activity of basal forebrain cholinergic neurons. The neurotrophin, nerve growth factor (NGF), enhances the survival effects of basal forebrain cholinergic neurons, which is retrogradely transported from cortex and hippocampus to the basal forebrain. Recent studies have shown that NGF plays a role in aging as well as in age-related diseases such as AD, since aging can interact with pre-existing abnormalities in trophic signalling to trigger cholinergic and cognitive decline as observed in AD. Further, gradual dysregulation of neurotrophic factors such as NGF and brain derived neurotrophic factor (BDNF) have been during AD development thus intensifying further research in targeting these factors as disease modifying therapies against AD. Today, there is no cure available for AD and the effects of the symptomatic treatment like cholinesterase inhibitors (ChEIs) and memantine are transient and moderate. Although many AD treatment studies have been carried out, there has as yet been no breakthrough and new therapies are thus highly needed. Therefore there is a need to review the new advancements in NGF research and its potential therapeutic implications in AD. In this review, we will put emphasis on NGF as a potential therapeutic factor with focus on encapsulated biodelivery (ECB) as a potential therapy method in AD. In summary, we hope to describe the experimental and clinical data, demonstrating the important roles of NGF for AD treatment, and encapsulated biodelivery as an efficient therapy for AD.